Adipose‐derived mesenchymal stem cells and regenerative medicine. (3rd March 2013) - Konno, Masamitsu; Hamabe, Atsushi; Hasegawa, Shinichiro; Ogawa, Hisataka; Fukusumi, Takahito; Nishikawa, Shimpei; Ohta, Katsuya; Kano, Yoshihiro; Ozaki, Miyuki; Noguchi, Yuko; Sakai, Daisuke; Kudoh, Toshihiro; et al.
<x xml:space="preserve">Abstract</x> Adipose tissue‐derived mesenchymal stem cells (ADSCs) are multipotent and can differentiate into various cell types, including osteocytes, adipocytes, neural cells, vascular endothelial cells, cardiomyocytes, pancreatic β‐cells, and hepatocytes. Compared with the extraction of other stem cells such as bone marrow‐derived mesenchymal stem cells (BMSCs), that of ADSCs requires minimally invasive techniques. In the field of regenerative medicine, the use of autologous cells is preferable to embryonic stem cells or induced pluripotent stem cells. Therefore, ADSCs are a useful resource for drug screening and regenerative medicine. Here we present the methods and mechanisms underlying the induction of multilineage cells from ADSCs.